Live Library Adventure @ SK Sageng, Simunjan / Celest Ludang Robert and Abdul Ismail Mohd Jawi - Robert, Celest Ludang; Mohd Jawi, Abdul Ismail (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Creating the Live Library Adventure Program (LLA) at Sekolah Kebangsaan Sageng was a journey of excitement and transformation, divided into two main phases: preparing and carrying out the program. The first phase was excitedly awaited as our team discussed potential solutions for the problems at SK Sageng, where a fire had destroyed the school's library. A shortage of reading resources and books made involvement necessary, particularly for the 270 students. Establishing a thriving resource center for the future was our clear objective.